KETERKAITAN ANTAR SUBSISTEM AGRIBISNIS JAGUNG HIBRIDA DI KECAMATAN MAJA - Syifa Herliani; Zumi Saidah; Trisna Insan Noor; Endah Djuwendah (Universitas Galuh Ciamis, 2021)
Corn is one of the crops that can be developed as an agro-industrial product because the competitiveness of corn is quite good and the selling value of corn is sufficient to increase the economic value of corn. Majalengka Regency is one of the largest maize production centers in Indonesia. Maja District is the largest producer of maize in Majalengka Regency. This research was conducted in Cihaur Village and Nunuk Baru Village, Maja District, Majalengka Regency. From the hybrid corn agribusiness sub-system, there are still problems that cause weaknesses and threats to the hybrid corn agribusiness subsystem, but it has the strength and opportunity for the development of hybrid corn agribusiness. For that, it is necessary to conduct a study to see the relationship between the hybrid corn agribusiness subsystem in Maja District. This study uses a qualitative descriptive analysis. Based on the research of the hybrid corn agribusiness subsystem, the five agribusiness subsystems are not related and their existence is still partial. For that we need a party that manages from upstream to downstream subsystems so that the subsystems are interrelated.